Pengaruh Komposisi Biochar dalam Kompos sebagai Bahan Pupuk Dasar dan sebagai Bahan Dasar Aplikasi Teh Kompos terhadap Pertumbuhan dan Hasil Bawang Putih (Allium sativum L) Siung Tunggal - Maria Yasintha Moti Fretis; Krisantus Tri Pambudi Raharjo; Eduardus Yosef Neonbeni (Fakultas Pertanian, Universitas Timor, 2019)
Single clove garlic has a relatively higher price than compound cloves, and has a high economic prospect. Some research results show that the decreasing limitations of growing space and resources, increase the formation of single cloves of garlic. Research has been carried out in May to September 2018 in the practice garden of the Faculty of Agriculture, University of Timor, to examine the effect of the composition of biochar in compost and compost biochar tea on the growth and yield of single cloves garlic in the middle plains. The study used factorial RAK 2 factors. The first factor is the composition of biochar in compost (B) consisting of 3 levels, namely: pure compost (B0), compost + biochar 10% (B1), compost + biochar 20% (B2). The material in the first factor was also applied as the second factor that was applied as a type of compost tea (T) consisting of 3 levels, namely: without compost tea (T0) pure compost tea (T1), compost biochar tea (T2), thus there were 9 plots treatment combination namely; B0T0, B0T1, B0T2, B1T0, B1T1, B1T2, B2T0, B2T1, and B2T2, which were repeated in 3 blocks so that there were 27 plots and 3 control plots resulting in a total of 30 plot plots. The results showed that giving 20% ​​biochar + compost and compost + biochar tea interacted positively (P <0.05), on the availability of soil organic matter, N-total, phosphorus (P), potassium (K), and cation exchange capacity (KPK). 10% biochar compost and Biochar Compost Tea increase the dry weight of single cloves per tuber.